Prevalence of Child Development Delay among Children Aged under 5 Years Old in Phatthalung Province - Kue-iad, Nuengruetai; Sangthong, Jirapong; Chaimay, Bhunyabhadh; Woradet, Somkiattiyos (Journal of Health Science of Thailand, 2019)
The objective of this retrospective descriptive study was to investigate the prevalence of delayed child development among children aged under 5 years old. The population of the study was children born in Phatthalung Province between January and December 2010. Totally, 1,182 children were included. They were followed and screened for the level of growth and development by health professional until 31 December 2015. The main variable was child development level which was classified into 3 groups as follow: (1) normal, (2) suspected-delayed development, and (3) delayed development. The data was analyzed by descriptive statistics. It was found that all children aged 1 - 3 years old had normal develop-ment. However, at aged 4 they were found to have normal, suspected-delayed and delayed development at the percentage of 99.75, 0.17 and 0.08, respectively. In addition, children aged 5 years old shows normal and delayed development at 89.26% and 10.74%, respectively. The findings suggested that de-layed development is increasingly common when children grow-up; and thus health professional should pay more attention on child development screening among children aged under 5 years old and continue to follow children with suspected-delayed development in order to promote and stimulate development so as to attain normal level, particularly among children aged at 4 and 5 years old. Such practice should reduce the prevalence of delayed child development delayed and prevent learning disability among school children.